Influence of early life exposure to social disadvantages on deliberate self-harm (DSH) among children of parents with mental health disorders - Nan Hu; Catherine Taylor; Rebecca Glauert; Jianghong Li; Janice Wong (International Journal of Population Data Science, 2017)
ABSTRACT